Self-Reported Sleep Disturbances in Patients with Dissociative Identity Disorder and Post-Traumatic Stress Disorder and How They Relate to Cognitive Failures and Fantasy Proneness - Van Heugten - Van Der Kloet, Dalena; Huntjens, Rafaele; Giesbrecht, Timo; Merckelbach, Harald (Frontiers in Psychiatry, 2014)
Sleep disturbances, fantasy proneness, cognitive failures, and dissociative symptoms are related to each other. However, the co-occurrence of these phenomena has been primarily studied in non-clinical samples. We investigated the correlations between these phenomena in dissociative identity disorder patients, post-traumatic stress disorder patients, and healthy controls. Both patient groups reported more sleep problems and lower sleep quality and displayed higher levels of fantasy proneness and cognitive failures than controls. However, the two patient groups did not differ with regard to these variables. Moreover, a higher level of unusual sleep experiences tended to predict participants belonging to the DID group, while specifically a lower sleep quality and more cognitive failures tended to predict participants belonging to the PTSD group.